Highly Efficient Catalytic Formation of (Z)‐1, 4‐But‐2‐ene Diols Using Water as a Nucleophile. (16th August 2016) - Guo, Wusheng; Martínez‐Rodríguez, Luis; Martin, Eddy; Escudero‐Adán, Eduardo C.; Kleij, Arjan W.
Abstract: The first general catalytic and highly stereoselective formation of (Z)‐1, 4‐but‐2‐ene diols is described from readily available and modular vinyl‐substituted cyclic carbonate precursors using water as a nucleophilic reagent. These 1, 4‐diol scaffolds can be generally prepared in high yields and with ample scope in reaction partners using a simple synthetic method that does not require the presence of any additive or any special precaution unlike the stoichiometric approaches reported to date. Control experiments support the mechanistic view that hyperconjugation within the catalytic intermediate after decarboxylation plays an imperative role to control the stereoselective outcome of these reactions.